Three little pigs - Down, Hayley; Saunders, Katie (Make Believe Ideas, Ltd., Berkhamsted, Herts (England), 2011, 2011)
An entertaining retelling of story of three little pigs, ideal for bedtime reading
English stories
Keywords: Children's stories